A quantitative comparsion of non-destructive testing surface techniques on metal specimens - Tang, Edric Tong Liang (2017)
In this report consists of three main topics regarding Non-Destructive Testing (NDT). During literature review, the main focus will be on NDT surface techniques such as visual testing (VT), liquid penetrant testing (LPT) and magnetic particle inspection (MPI). Nonetheless, another surface/sub-surface technique such as eddy current testing (ECT) will be briefly mentioned on its working principles and applications. At the later stage of the report, experiments and observations of liquid penetrant testing and magnetic particle inspection will be carried out on 5 different specimens. Optimum dwell time and bleed-out time will be investigated. Comparison of NDT techniques by using ImageJ to compare contrast values to determine best inspection technique. Lastly, the prospect and potential of developing an automated NDT surface technique will be discussed.